A STUDY ON HOW HUMAN RESOURCES MANAGEMENT PRACTICES INFLUENCE EMPLOYEE OUTCOMES - Nakhawa, Arya; M. S. Suganthiya; Sharma, Bhawana (International Journal of Research -GRANTHAALAYAH, 2025)
Human Resource Management (HRM) plays a crucial role in employee performance and organizational success in today’s business world. This research looks at how HRM practices, including recruitment and selection, training and development, performance appraisal, compensation, and employee engagement, affect employee outcomes like job satisfaction, motivation, productivity, retention, and commitment to the organization. A structured questionnaire was given to 120 employees in Mumbai and Pune, with 108 valid responses analysed using descriptive statistical methods. The findings show that well-designed HRM practices improve employee performance, loyalty, motivation, and overall job satisfaction. The study concludes that organizations need to implement strategic HRM systems to improve employee outcomes and maintain long-term competitiveness.